2008
DOI: 10.1111/j.1747-0765.2008.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of nitrogen fertilizer application rates based on soil nitrogen fertility with the goal of lowering nitrate nitrogen concentrations in Sudangrass (Sorghum sudanense(Piper) Stapf)

Abstract: High levels of nitrate nitrogen (NO 3 -N) in forage crops can poison ruminants. To promote stable production of Sudangrass (Sorghum sudanense (Piper) Stapf) with safe NO 3 -N levels, we investigated the influence of soil nitrogen (N) on Sudangrass yield and on NO 3 -N concentrations, and we propose a fertilizer management strategy based on soil N levels for a regime based on the application of cattle manure composted with sawdust. We used the available N content determined by incubation of fresh soil as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although these fertilizer applications improve dry matter (DM) production and crude protein (CP) content, excess nitrogen frequently leads to high nitrate nitrogen concentrations in grass. Sunaga et al (2008) reported high nitrate nitrogen in sudangrass (Sorghum sudanense (Piper) Stapf), which is the most popular annual summer grass in southwestern Japan. Therefore, there is the risk of a high nitrate nitrogen poisoning of palisadegrass as annual summer grass with fertilizer application at fertile soil in southwestern Japan.…”
mentioning
confidence: 99%
“…Although these fertilizer applications improve dry matter (DM) production and crude protein (CP) content, excess nitrogen frequently leads to high nitrate nitrogen concentrations in grass. Sunaga et al (2008) reported high nitrate nitrogen in sudangrass (Sorghum sudanense (Piper) Stapf), which is the most popular annual summer grass in southwestern Japan. Therefore, there is the risk of a high nitrate nitrogen poisoning of palisadegrass as annual summer grass with fertilizer application at fertile soil in southwestern Japan.…”
mentioning
confidence: 99%